Meningkatkan Hasil Belajar Siswa Kelas VIII C SMP Negeri 26 Banjarmasin Topik Cahaya dan Alat-Alat Optik Melalui Pengajaran Langsung - Zara Yahyana; Muhammad Arifuddin; Sarah Miriam (Berkala Ilmiah Pendidikan Fisika, 2017)
Application of learning model strategy in school is not in accordance with that expected to cause student learning outcomes is low. This study aims to improve student learning outcomes through direct teaching models. This study has a specific purpose to describe: (1) RPP implementation during teaching and learning activities, (2) students procedural skills, and (3) student learning outcomes. This study is a classroom action research consisting of two cycles. This research was conducted in SMP Negeri 26 Banjarmasin refers to the design of research flow PTK Kemmis and Mc Tagart with the subject of research is the students of class VIII C SMP Negeri 26 Banjarmasin. Data obtained through observation, tests, and documentation. Data analysis through quantitative anda qualitative descriptive. The resulrs showed that: (1) the implementation of RPP during the learning process through direct teaching model increased that is inn cycle I the percentage of implementation of RPP of 91,01% with very good category and on the second cycle of 96,33% with very good category, (2) students’ procedural skill are also classically increased, in cycle I percentage of 85,41% with very skilled category to be 95,48% in cycle II with highly skilled category, (3) student learning outcomes increase classically ie in cycle I percentage of learning outcomes students 62,5% with unfinished category to 87,5% with complete category in cycle II. The conclusion is obtained that through the direct teaching model can improve student learning outcomes.